Subjective Well Being Pada Penderita Diabetes Melitus (DM) Tipe II Di Srikandi Wound Care, Kabupaten Semarang - Ghilda Pricillia Hukom; Desi Desi; Venti Agustina (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Abstract Chronic diseases such as Diabetes Mellitus (DM) type II can cause profound psychological changes for patients, families and social groups. The positive view of DM sufferers about themselves is an indication of subjective well-being, on the other hand, DM sufferers themselves are an indication of low subjective well-being. Semarang Regency. This research was conducted at Srikandi Wound Care, Semarang Regency from March to April 2021. The method used in this study was qualitative, with data collection techniques using the Subjective Well Being interview guide instrument developed by Diener (2006). There were 5 participants who were determined using purposive sampling technique. The results of the study obtained 6 (six) themes that describe Subjective Well Being in type II DM patients, namely, respondents' experiences related to life satisfaction, happiness, respondents' feelings of sadness, family support, community views and respondents' knowledge regarding type II diabetes mellitus. In conclusion, subjective well-being in participants with Type II Diabetes Mellitus at Srikandi Wound Care refers to aspects of experience related to life satisfaction, participants' happiness, participants' sadness, family support, community views and knowledge related to type II diabetes mellitus.